2017
DOI: 10.2460/ajvr.78.12.1406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a high-fat–high-cholesterol diet on gallbladder bile acid composition and gallbladder motility in dogs

Abstract: OBJCTIVE To investigate the effects of dietary lipid overload on bile acid metabolism and gallbladder motility in healthy dogs. ANIMALS 7 healthy Beagles. PROCEDURES In a crossover study, dogs were fed a high-fat-high-cholesterol diet (HFCD) or a low-fat diet (LFD) for a period of 2 weeks. After a 4-month washout period, dogs were fed the other diet for 2 weeks. Before and at the end of each feeding period, the concentrations of each of the gallbladder bile acids, cholecystokinin (CCK)-induced gallbladder moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…High LDL can promote the formation of cholesterol polyps by lowering the sensitivity of gallbladder to cholecystokinin, which subsequent decreased gallbladder contraction, cholestasis and relative de ciency of cholic acid. [15][16][17] These physiological changes could promote cholesterol crystallization and polyp formation. While, Wu et al [8] found that TG, TC, HDL, and LDL showed no statistical differences between the cholesterol polyp group and the non-cholesterol polyp group, indicating that lipid levels may only play a partial role in the formation of cholesterol polyps.…”
Section: Discussionmentioning
confidence: 99%
“…High LDL can promote the formation of cholesterol polyps by lowering the sensitivity of gallbladder to cholecystokinin, which subsequent decreased gallbladder contraction, cholestasis and relative de ciency of cholic acid. [15][16][17] These physiological changes could promote cholesterol crystallization and polyp formation. While, Wu et al [8] found that TG, TC, HDL, and LDL showed no statistical differences between the cholesterol polyp group and the non-cholesterol polyp group, indicating that lipid levels may only play a partial role in the formation of cholesterol polyps.…”
Section: Discussionmentioning
confidence: 99%
“…LDL is representative of the status of liver anabolism and cholesterol transport. High LDL can promote the formation of cholesterol polyps by lowering the sensitivity of the gallbladder to cholecystokinin, which subsequently results in decreased gallbladder contraction, cholestasis, and a relative deficiency of cholic acid [15][16][17]. Meanwhile, the formation of cholesterol polyps may be related to abnormal reverse cholesterol transport related to HDL.…”
Section: Discussionmentioning
confidence: 99%
“…If there is abnormal bile secretion or functional impairment of the gallbladder, the bile contents stored in the gallbladder will change accordingly [ 12 ]. Several studies [ 13 , 14 ] have reported that dyslipidemia, such as high low-density lipoprotein, would decrease gallbladder sensitivity to cholecystokinin and inhibit cholecystokinin secretion, resulting in a reduction of gallbladder motility and alteration of the mucosal esterification of free sterols from bile. This physiological change in the hepatic cholesterol mechanism could then promote cholesterol polyp formation.…”
Section: Discussionmentioning
confidence: 99%